2017
DOI: 10.1016/j.dsr2.2016.05.028
|View full text |Cite
|
Sign up to set email alerts
|

Picturing thermal niches and biomass of hydrothermal vent species

Abstract: In community ecology, niche analysis is a classic tool for investigating species' distribution and dynamics. Components of a species' niche include biotic and abiotic factors.In the hydrothermal vent ecosystem, although composition and temporal variation have been investigated since these deep-sea habitats were discovered nearly 40 years ago, the roles and the factors behind the success of the dominant species of these ecosystems have yet to be fully elucidated. In the Lucky Strike vent field on the Mid Atlant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
43
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 31 publications
(53 citation statements)
references
References 99 publications
7
43
2
Order By: Relevance
“…They form dense faunal assemblages in relatively low-temperature microhabitats (De Busserolles et al, 2009;Cuvelier et al, 2011a). A spatial segregation in mussel sizes is observed with a decrease in size with increasing distance from hydrothermal input and corresponding thermal gradient showing diet changes with mussel size categories (Husson et al, 2017). Contrastingly to what has been described by Sarrazin et al (2014), no significant interactions between mussels and other organisms were observed based on the 6 h frequency analysed here.…”
Section: Engineering Speciescontrasting
confidence: 53%
“…They form dense faunal assemblages in relatively low-temperature microhabitats (De Busserolles et al, 2009;Cuvelier et al, 2011a). A spatial segregation in mussel sizes is observed with a decrease in size with increasing distance from hydrothermal input and corresponding thermal gradient showing diet changes with mussel size categories (Husson et al, 2017). Contrastingly to what has been described by Sarrazin et al (2014), no significant interactions between mussels and other organisms were observed based on the 6 h frequency analysed here.…”
Section: Engineering Speciescontrasting
confidence: 53%
“…They form dense faunal assemblages in relatively low-temperature microhabitats (De Busserolles et al, 2009;Cuvelier et al, 2011a). A spatial segregation in mussel sizes is observed with a decrease in size with increasing distance from hydrothermal input and corresponding thermal gradient showing diet changes with mussel size categories (Husson et al, 2017). Contrastingly to what has been described by Sarrazin et al (2014), no significant interactions between mussels and other organisms were observed based on the 6 h frequency analysed here.…”
Section: Engineering Speciescontrasting
confidence: 50%
“…Four species of Bathymodiolus inhabit vent sites on the MAR (Van Cosel et al, 1999;van der Heijden et al, 2012). PLDs of Bathymodiolus mussels vary 500 from 3-4 months for the dominant species on the northern MAR Bathymodiolus azoricus (Colaço et al, 2006;Husson et al, 2016), to more than a year for Bathymodiolus childressi (Arellano and Young, 2009). As Bathymodiolus' eggs are slightly negatively buoyant (although not precisely quantified, Arellano and Young, 2009), they are not likely to spread upon release otherwise than through 505 their entrainment in the rising vent plume, which extends 300-500 m above the source (Speer and Marshall, 1995;Wilson et al, 1996).…”
Section: Discussion On the Connectivity Between Hydrothermal Ventsmentioning
confidence: 99%
“…Considering their egg size and body length, Bathymodiolus fecundity can reasonably be assumed to be at least in the same order of magnitude as in coastal mytilids, which can release more than 10 6 eggs/female/spawning season (Sprung, 1983). The average 570 density of sexually mature mussels (i.e., exceeding 3 cm body length, Colaço et al, 2006) is 10 3 ind m −2 (Cuvelier et al, 2011a;Husson et al, 2016), half of them being females. Estimating the surface covered by these mussels to be about 10 m 2 in Eiffel Tower (Figure 3 in Cuvelier et al (2009) andCuvelier et al (2011b)), we grossly estimate that 5000 mature females may spawn their 575 eggs each season at this edifice.…”
mentioning
confidence: 99%